Surface Structure and Electron Transfer Dynamics of the Self-Assembly of Cyanide on Au{111} - Guttentag, Andrew I; Wächter, Tobias; Barr, Kristopher K; Abendroth, John M; Song, Tze-Bin; Sullivan, Nichole F; Yang, Yang; Allara, David L; Zharnikov, Michael; Weiss, Paul S (Journal of physical chemistry. C, 2016)
A vibronic resonance between Au{111} surface states and adsorbed CN vibrations has been predicted, which we target for study. We have formed stable monolayers of cyanide on Au{111} and observe a hexagonal close-packed lattice with a nearest neighbor distance of 3.8 ± 0.5 Å. Cyanide orients normal to the surface attached via a Au–C bond. We show that the substrate–molecule coupling is particularly strong, leading to ultrafast electron transfer from the cyanide molecules to the Au{111} substrate as measured by resonant Auger spectroscopy using the core–hole clock method. The CN/Au{111} system is a simple example of a strongly interacting adsorbate–substrate system and will be the subject of a number of further studies, as discussed.